Readiness for Total Quality Management Implementation and Its Association with Product Quality and Production Efficiency: A Case Study of Raja Rasa Traditional Snack MSME - Hakim, Moh. Lukman; Daud, Moh. Yusuf; Djohar, Noor (Kadiri University - Faculty of Agriculture, 2026)
This study aims to assess the readiness for the implementation of Total Quality Management (TQM) and explore its relationship with product quality and production efficiency in a micro, small and medium enterprise (MSME) producing snacks through a single case study approach, which has limitations in terms of generalization. The respondents involved were owners and employees (n = 4) who were selected purposively. TQM readiness was measured using an instrument based on five dimensions, namely customer focus, continuous improvement, employee involvement, leadership, and process management, which were adapted from the TQM conceptual framework and measured using a 1–5 Likert scale. The readiness index was calculated using a simple unweighted average, with the following categories: 1.0–2.0 (not ready), 2.1–3.0 (not very ready), 3.1–4.0 (quite ready), and 4.1–5.0 (ready). Product quality and production efficiency were evaluated based on respondents' views, supported by direct observation of the production process to reduce bias in internal reports. This analysis was performed using descriptive and Spearman's rank correlation statistics. The findings of this study show that the readiness index is 4.00, product quality is 3.66, and production efficiency is 3.16. The identified relationship shows a positive connection between TQM readiness and product quality (ρ = 0.632) and production efficiency (ρ = 0.775). Pareto analysis found three main factors causing production problems—raw material instability (30%), lack of Standard Operating Procedures (SOP) (16.67%), and defective products (13.33%)—which contributed to 60% of total incidents. The results of this study provide a readiness profile and identify priority gaps in process management, emphasizing the importance of implementing operational standards to improve production efficiency.